PSYCHOLOGICAL EFFECTS OF COLORS AND COLOR THERAPY: रंगों का मनोवैज्ञानिक प्रभाव एवं रंग चिकित्सा - Saxena, Sangita (International Journal of Research -GRANTHAALAYAH, 2014)
The entire fabric of life is made of colors, whether our clothes are yes, home, or car. Everyone is identified with colors. Colors have specific effects on human life and mind. Color is a valuable gift of nature and also the beauty of human life. The redness of the dawn, the blue sky, the gray mountains, the straw, the green plants and the trees, the turquoise sea - everything unique and wonderful. The relationship between man and nature is also unbreakable. Sometimes Basanti yellow, sometimes greenery sawan, sometimes Sitabh and sometimes Tamavruta night. This is also the journey of man's life. Sometimes golden hope and sometimes disappointment. The cloudy sky blurts the mind as well, the rays of the sun rip it off, making everything clear. If there is no color in life, then it will become very dry and dry. जीवन का समूचा ताना-बाना रंगों से बना है, चाहे हमारे वस्त्र हांे, घर हो, या गाड़ी हो। सबकी पहचान रंगों के साथ है। रंगों का मनुष्य के जीवन और मन पर विशिष्ट प्रभाव होता है। रंग प्रकृति की बहुमूल्य देन है और मानव के जीवन का सौंदर्य भी। उषाकाल की लालिमा, नीलाभ नभ, भूरे पहाड़, तिनकों, पौधों और पेड़ों की हरिताभा, फीरोज़ी समुद्र- सबकुछ विशिष्ट और अद्भुत। मनुष्य और प्रकृति का संबंध भी अटूट है। कभी बसंती पीला तो कभी हरियाला सावन, कभी सिताभ तो कभी तमावृता रात। ऐसे ही मनुष्य की जीवन-यात्रा भी है। कभी सुनहली आशा तो कभी निराशा की कालिमा। मेघाच्छादित आकाश मन को भी धुँधला देता है तो उसे चीरती सूर्य की किरण, सबकुछ स्पष्ट करने वाली। यदि जीवन में रंग न हांे तो बहुत शुष्क और नीरस हो जाए।